Characterisation of EMS mutagenic bread wheat (Triticum aestivum l.) lines to investigate their water deficit stress tolerance and adaptability - Kayaga, Helen Ninsiima (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhDAgric)--Stellenbosch University, 2023.